Recent salinity intrusion in the Bengal delta: Observations and possible causes. (1st November 2020) - Sherin, V.R.; Durand, Fabien; Papa, Fabrice; Islam, AKM Saiful; Gopalakrishna, V.V.; Khaki, M.; Suneel, V.
Abstract: Salinization stands among the most prominent environmental hazards of the largest delta on Earth, the Bengal delta. It has significant impacts on the local societies and the economy. Using an unprecedented collection of in situ river salinity records over the Bengal delta, extending from the Hooghly estuary in the west to the Meghna estuary in the east, we report a sudden salinization of the central part of the delta that occurred in 2006–2007. This results in a sudden landward shift of the seasonal march of the salinity front by about 20 km, taking place in the pre-monsoon season. Such a regime shift was never reported before. We investigate the various drivers of this sudden change and identify three possible forcing factors: the decrease in Ganges freshwater discharge, the rise of sea level and the depletion of the groundwater level. These factors may act independently, or in concert. Given the threat of the ongoing climate change and its cohort of adverse effects expected in the course of the 21st century in the Bengal delta, our study contributes to set the observational basis for the development of the next generation of salinization modeling platforms. Highlights: A novel consolidated in situ salinity dataset is analyzed over the Bengal delta. Sudden salinization of the central part of the Bengal delta occurred in 2006–2007. Sudden landward progress of the salinity front of about 20 km. This shift is commensurate with what is expected over centennial timescales. Several factors identified as drivers of this abrupt salinization.